A novel broadband terahertz filter for photonic crystal. Issue 17 (24th September 2016) - Luo, Yuan; Li, Yanyan; Hu, Zhangfang; Liu, Jinlan
Abstract: The influence of the change of the radius of point defect cylinders, scattering dielectric cylinders, dielectric cylinders on both sides of line waveguide on S parameter is studied. According to the resonant coupling principle between micro-cavity and waveguide, a novel broadband terahertz filter is designed. The novel filter is formed by introducing scattering dielectric cylinders into the resonant microcavity, and the point defect cylinders are composed of HgTe material and adjusting the radius of dielectric cylinders on both sides of line waveguide. Results show that the 3 dB bandwidth reaches 74.2 GHz, the return loss is less than −12.02 dB, the maximum insertion loss in-band reaches 0.35 dB and its drop efficiency is up to 96.79%. The novel terahertz filter has flat passband, sharp rejections at out-bands and its central frequency is 0.338THz. The good performances show that it can meet the requirements of high speed and broadband in terahertz atmosphere communication I window.